(3eNJUQ GdeNJUQ aj CNHGQ GdHTQ dCHi GdaOGAs - (3eLghds; (3ESeGYjd Mbj , ESeGYjd Mbj Hf eUWaj GdGSdGeHhdj GdMfaj GdNdhJj, CHh GdaOGA,J (B1127 (3g` s
(3ChdgG (B:s
(3ef bHjd GdaUd GdQGHY ai edhc GdYQH s
(3BNQgG (B:s
(3SfI (B430 (3ajgG Jhaj CHh Ydi GdMSjf GdQNLi hRjQ s
(3HgG WeSs
(3gfGc Tc aj fSHI cJGH (B" (3GdeNJUQ aj CNHGQ GdHTQ (B" (3Edi CHj GdaOGAs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B266s
Keywords: (3GdJGQjNs